Molecular Insights into Sex Differentiation of Rhinogobio nasutus via Integrated mRNA and miRNA Profiling - Jie Yin; Yanbin Liu; Muhammad Jawad; Haijing Xu; Muyan Li; Zongqiang Lian; Mingyou Li (Fishes, 2026)
Rhinogobio nasutus, an endangered fish species endemic to the upper and middle reaches of the Yellow River in China, lacks essential genomic information on gonadal development, hindering research into its reproductive biology. To address this, mRNA-seq and miRNA-seq datasets derived from adult testis (n = 3) and ovary (n = 3) were integrated to characterize sex-biased expression profiles and potential regulatory mechanisms. A total of 34,813 genes and 68,623 transcripts were detected, and 16,105 differentially expressed genes (DEGs) were identified between testis and ovary, including 9365 testis-biased and 6740 ovary-biased genes. Small-RNA profiling identified 51 differentially expressed miRNAs (DEMs: 31 testis-biased; 20 ovary-biased). The sex-biased mRNA profiles highlighted conserved candidate genes associated with germ-cell maintenance, somatic regulation, ovarian differentiation, and oocyte maturation, including vasa, piwi, dmrt1, amh, cyp19a1a, zar1, zar1l, and rbpms2. Integrated miRNA–mRNA analysis further predicted potential interactions involving key sex-related genes, suggesting that DEMs may contribute to post-transcriptional regulation during gonadal differentiation. Functional enrichment (GO and KEGG analyses) highlighted pathways associated with gonadal differentiation, germline maintenance, and signal transduction pathways. qRT-PCR validation of nine mRNAs and nine miRNAs showed expression patterns consistent with the sequencing results. Collectively, these results provide an integrated mRNA and miRNA resource for R. nasutus gonads and identify candidate genes and miRNAs for future studies on sex-biased gonadal development, reproductive regulation, and artificial propagation.